The soft side of environmentally-sustainable organizations. Issue 4 (8th October 2018) - Jabbour, Charbel Jose Chiapetta; Renwick, Douglas William Scott
Abstract : Purpose: The purpose of the paper is to present a discussion on the "soft and human" side of building environmentally sustainable organizations, a flourishing management subfield called "green human resource management" (GHRM), which concerns alignment of people and environmental management objectives of organizations. Design/methodology/approach: The authors reviewed some of the most relevant research results in GHRM. Findings: In this paper, the authors define GHRM, its workplace-based practices and some recent developments' evidence on the positive impact of it on firms' ecological objectives. The authors conclude by detailing a new research agenda in GHRM. Originality/value: The authors conclude by detailing a new and contemporary research agenda in GHRM.